Kalkitoxin: A Potent Suppressor of Distant Breast Cancer Metastasis - Shrestha, Saroj Kumar; Min, Kyung Hyun; Kim, Se Woong; Kim, Hyoungsu; Gerwick, William H.; Soh, Yunjo (International Journal of Molecular Sciences, 2023)
Bone metastasis resulting from advanced breast cancer causes osteolysis and increases mortality in patients. Kalkitoxin (KT), a lipopeptide toxin derived from the marine cyanobacterium Moorena producens (previously Lyngbya majuscula), has an anti-metastatic effect on cancer cells. We verified that KT suppressed cancer cell migration and invasion in vitro and in animal models in the present study. We confirmed that KT suppressed osteoclast-soup-derived MDA-MB-231 cell invasion in vitro and induced osteolysis in a mouse model, possibly enhancing/inhibiting metastasis markers. Furthermore, KT inhibits CXCL5 and CXCR2 expression, suppressing the secondary growth of breast cancer cells on the bone, brain, and lungs. The breast-cancer-induced osteolysis in the mouse model further reveals that KT plays a protective role, judging by micro-computed tomography and immunohistochemistry. We report for the first time the novel suppressive effects of KT on cancer cell migration and invasion in vitro and on MDA-MB-231-induced bone loss in vivo. These results suggest that KT may be a potential therapeutic drug for the treatment of breast cancer metastasis.
Keywords: Animals; Cell Line, Tumor; Cell Movement; Lipids; Mice; Neoplasm Metastasis; Osteoclasts; Osteolysis; X-Ray Microtomography; an anti-cancer medicine; breast cancer; EMT markers; kalkitoxin; metastasis